Polynomial Calculator

Top
**Step 1 :** Identify the values of a, b, and c; a is the coefficient of x^2, b is the coefficient of x, and c is the constant.

**Step 2 :** Find the discriminant (D) = b^2 - 4ac.

**Step 3 :** If the discriminant is positive(D > 0) , the expression has two real solutions given by.

x1 = (-b)+sqrt(D)/2a.

x2 = (-b)-sqrt(D)/2a.

**Step 4 :** Factors are (x+x1)(x+x2).

Polynomial Calculator (or Polynomial Solver) is an online tool to find the factors of a polynomial.

Please go through the list of calculators related to polynomials below.

Below is given four different polynomial calculators. In the first calculator, click on "Calculate", either addition or subtraction of polynomial between the given default first and second polynomial is calculated.

In the second calculator, click on "Multiply", multiplication of polynomial between the given default first and second polynomial is calculated.

In the third calculator, click on "Divide", division of polynomial between the given default first and second polynomial is calculated.

In the fourth calculator, click on "Calculate", derivative or integral of default polynomial is calculated.

x1 = (-b)+sqrt(D)/2a.

x2 = (-b)-sqrt(D)/2a.

### Factor x^2+3x-4.

**Step 1 :**In the above equation, a(coefficient of x^2)=1,b(coefficient of x)=3,c(constant)=-4.**Step 2 :**D= b^2 - 4ac.

D= 3^2 - 4(1)(-4).

D= 9 - (-16).

D= 25.**Step 3 :**D > 0, the expression has two real solutions given by.

x1 = (-b)+sqrt(D)/2a.

x1 = (-3)+sqrt(25)/2(1) = (-3+5)/2.

x1 = 1.

x2 = (-b)-sqrt(D)/2a.

x2 = (-3)-sqrt(25)/2(1) = (-3-5)/2..

x2 = -4.**Step 4 :**Factors are (x-1)(x+4)**Answer :**(x-1)(x+4)### Factor x^2+5x+6.

**Step 1 :**In the given equation, a(coefficient of x^2)=1,b(coefficient of x)=5,c(constant)=6.**Step 2 :**D= b^2 - 4ac.

D=5^2 - 4(1)(6).

D=25 - 24.

D= 1.**Step 3 :**Since D > 0, the expression has two real solutions given by.

x1 = (-b)+sqrt(D)/2a.

x1 = (-5)+sqrt(1)/2(1)= (-5+1)/2.

x1 = -2.

x2 = (-b)-sqrt(D)/2a.

x2 = (-5)-sqrt(1)/2(1)= (-5-1)/2.

x2 = -3.**Step 4 :**Factors are (x+2)(x+3)**Answer :**(x+2)(x+3).